Proyecto de factibilidad para la creación de una avícola en la comuna Maca Grande. - Ayala Unaucho, Keni Rommel (2024)
The research has raised a general objective which is to evaluate economic, technical, financial and social viability the creation of a poultry farm in Maca Grande commune, In this way produce organic eggs, with products purely from the area. It should be noted that the business idea has a similarity in many investigations where information has been obtained in different thesis, At the same time, all the terms that will be used have been determined, based on the authors, in the market study a survey has been proposed to determine supply and demand, as well as price projections, specific place where the poultry farm can be implemented, some of the data where the information has been obtained has been in the CONAVE ´´National Corporation of Poultry Farmers of Ecuador´´ within the technical study, factors such as product, organization chart, macro, micro location were determined, including the description of the plant where a possible infrastructure was designed for the implementation, also it was considered the logo the poultry plant. In the economic-financial study, factors such as initial investment, production costs, income statements, financial statements were obtained, then determining the (MARR), with 21.51%, a NPV of 4,163.72% and an (IRR) of 26.78% considering that it gives a positive signal for the research, to finish the research the respective comparison has been made considering that The (IRR) must be greater than the (MARR) and the (NPV) greater than (ONE) where compliance with this regulation has been achieved. Keywords: Feasibility Project, economic study, financial, production, marketing, organic eggs.